2017
DOI: 10.2196/formative.8370
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Asbestos-Containing Materials in Homes: Design and Development of the ACM Check Mobile Phone App

Abstract: Background Asbestos-containing materials (ACMs) can still be found in many homes in Australia and other countries. ACMs present a health risk when they are damaged or disturbed, such as during do-it-yourself home renovations. However, community members lack knowledge and awareness about asbestos identification and its safe management in residential settings. Objective The objective of our study was to describe the process of developing a mobile phone app, ACM Check, tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…EHOs may be attending or screening more 'at-risk' properties than the average community member due to the nature of their job. In addition, our pilot study showed that ACM Check users tended towards overestimating the priority of ACMs in and around their home (i.e., they frequently rated materials as being in poorer condition or having a higher potential for disturbance than did the environmental consultant) [19]. As such, it is unlikely that these results are underestimating the priority levels of the ACMs screened in this sample.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…EHOs may be attending or screening more 'at-risk' properties than the average community member due to the nature of their job. In addition, our pilot study showed that ACM Check users tended towards overestimating the priority of ACMs in and around their home (i.e., they frequently rated materials as being in poorer condition or having a higher potential for disturbance than did the environmental consultant) [19]. As such, it is unlikely that these results are underestimating the priority levels of the ACMs screened in this sample.…”
Section: Discussionmentioning
confidence: 75%
“…All data collection occurred through the mobile app, ACM Check, between 13 June 2017 and 14 September 2019. A detailed description of the design and development of ACM Check has been published elsewhere [19]. In short, the app contains a questionnaire that guides users through a visual inspection of 14 key locations inside and outside of a residential building.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, statistics were also employed in study inspection reports and online demolition databases to quantify the amounts and abatement costs for asbestos-containing materials in abandoned residential dwellings by Franzblau et al [6]. Govorko et al [2,16] developed a mobile application to investigate the types and the conditions of asbestos-containing materials in residential settings.…”
Section: Introductionmentioning
confidence: 99%
“…Australia was the highest consumer of asbestos on a per capita basis during the mid-20 th century, (10) and it is likely that almost all Australian households built prior to 1990 contain some form of asbestos. (11) As such, it is important to raise people's awareness and knowledge of where ACMs can be located in the residential environment in order to prevent inadvertent asbestos exposure arising from these sources. However, asbestos cement products are notoriously difficult to identify and many home-owners have a low level of confidence when it comes to identifying ACMs in and around the home.…”
Section: Introductionmentioning
confidence: 99%